ANALYSIS OF FACTORS AFFECTING AUDIT DELAY IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING COVID 19 - Yuha Nadhirah Qintharah; Puspita Sari (Journal of Global Business and Management Review, 2023)
Audit delay can affect the level of relevance of information from a financial report, because the longer the time it takes to conduct an audit, the level of relevance of the information can be doubted. The length of the audit completion process can affect audit delay in submitting audited financial reports so that it can have an adverse impact on market reactions and cause uncertainty in economic decision making. The research model used in this research is quantitative. With a research sample of non-silica (food and beverage) sector companies because companies that experience fluctuating financial performance tend to decline during the Covid 19 pandemic. The data analysis technique uses multiple linear regression with the SPSS program. The results of the study state that the auditor's opinion has no significant effect on audit delay, audit tenure has no significant effect on audit delay, company size has a significant effect on audit delay.